Analisis Kinerja Keuangan Badan Usaha Milik Negara Sebelum dan Sesudah Privatisasi Tahun 2001-2013 - ARIZKY, ERIE ARIZKY B1021141052 (Jurnal Manajemen Update, 2018)
Since three decades privatization has become a controversial issue and wide spread phenomenom both in developed and developing countires. It was believed that privatization is an effective method for improving the performance and efficiency of State-Owned Enterprises (SOE’s). In Indonesia, it aims not only to improve the SOE’s performance and efficiency, but also as a means to increase public participation through stock ownership. The purpose of this study is to compare the financial performance before and after the privatization of 14 (SOE’s) in 8 sub-sectors that privatized through Initial Public Offering (IPO) between 2001 and 2013. The results of Paired Sample T-test showed that after privatization liquidity is found increase insignificantly, while leverage and profitability measured by Return On Equity (ROE) decreased significantly, except for Return On Asset (ROA). Efficiency level shows different result depend on the measurement, it decreased significantly measured by Total Aset Turnover (TATO) but it turns out to be significantly positive when measured by Sales Efficiency (SALEF) and Net Income Efficiency (NIEF).Key Words: Privatization, Financial performance, BUMN